Global regurgitant volume: approaching the critical mass in valvular-driven heart failure. (29th June 2019) - Bartko, Philipp E; Arfsten, Henrike; Heitzinger, Gregor; Pavo, Noemi; Spinka, Georg; Kastl, Stefan; Prausmüller, Suriya; Strunk, Guido; Mascherbauer, Julia; Hengstenberg, Christian; Hülsmann, Martin; Goliasch, Georg
Abstract: Aims: Recent progress in the diagnosis of functional valve regurgitation forms a coherent perception of severity thresholds by quantitative assessment. However, thresholds focused on either valve in isolation—not accounting for the global haemodynamic burden arising from concomitant functional regurgitation of the mitral and tricuspid valves. We sought to determine whether the global regurgitant volume is associated with adverse cardiac remodelling and mortality. Methods and results: This long-term observational study included 414 patients on guideline-directed medical therapy. Baseline global regurgitant load defined as the sum of mitral and tricuspid regurgitant volume was assessed by the proximal flow convergence method. All-cause mortality during 5 years follow-up served as the primary endpoint. The median global regurgitant load was 30 mL (interquartile range 15–49) with 67% accounting for mitral and 33% accounting for tricuspid regurgitant volume. The global regurgitant load had significant impact on outcome with a crude hazard ratio of 1.46 (1.28–1.66; P < 0.001) for a 1-SD increase in global regurgitant volume, results that remained virtually unchanged after bootstrap or clinical confounder-based adjustment (P < 0.001 for adjusted models). Spline curve analysis showed a linearly increasing risk with a threshold of 50 mL and sustained increasing risk thereafter. Conclusions: The present study demonstrates the detrimental effect of the global regurgitant load in patients with heart failure with reduced ejection fraction. The threshold where heart failure is driven by the valve lesions is a global regurgitant volume of 50 mL with continuously increasing risk beyond that threshold. Future studies need to address whether an attempt to reduce the global regurgitant volume can improve outcome.